The Effect of Work-Study Conflict on Student Engagement in Working Student - Auliya, Haifa; Yudhaningrum, Lupi; Maulana, Herdiyan; Nuradhi, Mohamad Abdilah (Merpsy Journal, 2025)
This research aims to determine the effect of work-study conflict on student engagement in working students. The subjects of this research were 266 undergraduate students in Indonesia who were actively working. Sampling used a non-probability sampling technique with a purposive sampling method. The research method used is a quantitative method with simple linear regression. The data collection technique uses a questionnaire with a Likert scale. The measuring tool uses the Student Engagement Scale by Nilna Mafaza, Fajar Kawuryan, and Ridwan Budi Pramono in 2021 and the Work-Study Conflict Scale by Rizky Rahmatul Zamarni in 2022. The results show that there is a negative and significant influence of work-study conflict on student engagement in students working. This means that if work-study conflict decreases, student engagement increases. The work-study conflict variable contributed to student engagement by 42.7%, while the remaining 57.3% was influenced by other factors not examined in this research. The majority of partisipants were in the category of high student engagement and low work-study conflict.